A case of primary ovarian signet-ring cell carcinoma treated with S-1/CDDP therapy - Tadahiro Shoji; Ryosuke Takeshita; Tatsunori Saito; Takeshi Aida; Shunichi Sasou; Tsukasa Baba (BMC, 2020)
Abstract Background Primary ovarian signet-ring cell carcinoma is extremely rare, with only five recent case reports. Almost all reported cases of ovarian signet-ring cell carcinoma have been treated with TC therapy and none have reported regarding the use of S-1/CDDP therapy. We report a case of primary ovarian signet-ring cell carcinoma treated postoperatively with S-1/CDDP therapy. Case presentation We describe a 55-year-old woman diagnosed with stage IB primary ovarian signet-ring cell carcinoma that was treated with S-1/CDDP therapy. Preoperative transvaginal ultrasonography and contrast-enhanced computed tomography (CT) revealed a solid tumor measuring 10 cm in diameter in the pelvis. The tumor marker levels were as follows: CA125, 41.6 U/mL; CA19-9, < 2.0 U/mL; and CEA, 2.2 ng/mL. Ovarian cancer was suspected, and total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy were performed. The left ovary was enlarged to greater than fist-sized, and there was a small amount of clear yellow ascites. Histological examination of the left ovary led to the diagnosis of signet-ring cell carcinoma. Histological examination of the right ovary also showed the presence of a signet-ring cell carcinoma. After surgery, upper and lower gastrointestinal endoscopy and positron-emission tomography-CT were performed to search for a possible primary lesion, but none was found. The patient was diagnosed with primary ovarian signet-ring cell carcinoma with FIGO Stage IB (PT1b, NX, M0). As postoperative adjuvant chemotherapy, S-1/CDDP therapy (S-1120 mg/day/body × 14 days, CDDP 50 mg/m2 day 8, q 21 days) was administered for six cycles. There was no recurrence 27 months after the initial treatment. Conclusions We considered S-1/CDDP therapy was effective for primary ovarian signet-ring cell carcinoma. This is the first case report of primary ovarian signet-ring cell carcinoma treated with S-1/CDDP therapy in the world.